Radio frequency modulation made easy - Faruque, Saleh (Springer, 2017)
"This book introduces Radio Frequency Modulation to a broad audience. The author blends theory and practice to bring readers up-to-date in key concepts, underlying principles and practical applications of wireless communications. The presentation is designed to be easily accessible, minimizing mathematics and maximizing visuals"--Provided by publisher.
Keywords: Radio frequency modulation.; elektronické knihy; electronic books